2005
DOI: 10.1186/1471-2458-5-33
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to and management of fertility among primary health care physicians in Turkey: An epidemiological study

Abstract: BackgroundThe subject of infertility has taken its place in the health sector at the top level. Since primary health care services are insufficient, most people, especially women, keep on suffering from it all over the world, namely in underdeveloped or developing countries.The aim of this study was to determine primary care physicians' opinions about the approach to infertility cases and their place within primary health care services (PHCSs).MethodsThe study was conducted between October 2003 and April 2004.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
4
5
3
Order By: Relevance
“…More than 3 quarters of family physicians (77%) included within this study viewed the PHC as an appropriate place for infertility management. The present results were better than that found by Hassa et al [ 14 ] about attitudes to and management of fertility among primary health care physicians in Turkey and in the study by Ittner et al [ 8 ] about German family physicians' attitudes toward care of involuntarily childless patients (38.9% and 27.0%) respectively. The different results could be related to the perceived importance of infertility management by the studied sample, as it is a main topic in the curriculum of family medicine.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…More than 3 quarters of family physicians (77%) included within this study viewed the PHC as an appropriate place for infertility management. The present results were better than that found by Hassa et al [ 14 ] about attitudes to and management of fertility among primary health care physicians in Turkey and in the study by Ittner et al [ 8 ] about German family physicians' attitudes toward care of involuntarily childless patients (38.9% and 27.0%) respectively. The different results could be related to the perceived importance of infertility management by the studied sample, as it is a main topic in the curriculum of family medicine.…”
Section: Discussioncontrasting
confidence: 94%
“…Regarding treatment and providing information to infertile cases, physicians could perform from (44.0%) for treatment of sexually transmitted diseases to (91.0%) for appropriate referral while their practice ranged from (20.0%) for treatment of hyperandrogenemia to (85.3%) for appropriate referral. These results were not similar to that of the Turkey study [ 14 ] as physicians reported the ability to perform from (26.2%) for hormonal treatment for male factor to (92.2%) for treatment of sexually transmitted diseases. This means underperformance in the present study than in the turkey study which could be related to inadequate training in intervention processes by the studied physicians.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations